Comparison of ketoacidosis in type 1 and 2 diabetic patients with and without concurrent COVID-19 and determining the factors affecting their treatment and survival: a retrospective cohort study - Ahmed, Asma; Badini, Kaleemullah; Khalid, Farah; Sohail , Sahlah; Salik, Muhammad (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the incidence of diabetic ketoacidosis in coronavirus disease-2019 patients and their survival rate, and to compare their outcomes with diabetic ketoacidosis patients without coronavirus disease-2019. Method: The retrospective cohort study was conducted at Aga Khan University Hospital, Karachi, and comprised data March 1, 2020, to March 31, 2021, related to patients. who had diabetic ketoacidosis with coronavirus disease-2019 in group A, and those who had diabetic ketoacidosis without coronavirus disease-2019 in group B. Data included age, gender, duration and type of diabetes and the final outcome. Data was analysed using SPSS 25. Results: Of the 120 patients, 40(33.3%) were in group A; 21(52.5%) males and 19(47.5%) females, with 22(55%) aged 45-64 years. There were 80(66.6%) patients in group B; 42(52.5%) males and 38(47.5%) females, with 36(45%) aged <45 years (p>0.05). The mortality was higher in group A patients13(32.5%) compared to those in group B 10(12.5%) (p<0.05). The data analysis was performed with the Statistical Package for Social Sciences (SPSS), V.25. Survival analysis showed that age, dyslipidaemia, history of cardiac revascularisation, acute respiratory distress syndrome, ventilator requirement, and severity of coronavirus disease-2019 were significantly associated with mortality (p<0.05). Conclusion: Patients of diabetic ketoacidosis with coronavirus disease-2019had poor survival outcomes compared to diabetic ketoacidosis patients without coronavirus disease-2019. Key Words: Diabetes mellitus, Diabetic ketoacidosis, COVID-19, Mechanical ventilator, Acidosis.